Design, synthesis, and in vitro evaluation of a carbamazepine derivative with antitumor potential in a model of Acute Lymphoblastic Leukemia - Cristian Álvarez-Gómez; Angela V. Fonseca-Benitez; James Guevara-Pulido (PLoS ONE, 2025)
Acute lymphoblastic leukemia (ALL) is a significant concern in both pediatric and adult demographics. Despite 156 approved cancer therapies based on small molecules, a mere five apply to all types of leukemia. Unfortunately, adherence to these treatments is low due to adverse side effects. Consequently, there is an urgent need to identify more effective treatment options for ALL. This study presents a potential solution. We have designed over fifty analogs of carbamazepine, utilizing a combination of ligand-based and structure-based drug design methodologies. Among these analogs, we identified the CR80 analog, which demonstrated predicted binding values of -8.66 kcal/mol against beta-tubulin, a favorable LogP, and IC50 values suitable for in vitro evaluation. The CR80 compound was synthesized with a yield of 50% and subsequently assessed in vitro against the U-937 cell line. It obtained an IC50 value of 0.8 micromolar to 1 micromolar and a selectivity index of two, thus marking it as a promising candidate for in vivo studies.